Cultural competence in diversity management: a case study in a public library - Silva, Bruna Daniele de Oliveira [UNESP]; Camillo, Everton da Silva [UNESP]; Guaraldo, Tamara de Souza Brandão [UNESP] (Universidad Nacional de La Plata, 2023)
The paper has as a theoretical framework the diversity management and cultural competence. It aims to identify ways omanaging diversity in a public library in the interior of the state of São Paulo, establishing a theoretical reflection between thi management and the development of cultural competence in the organization. The relations between the purposes of organizational planning and the actions developed by the library team, was evaluated. The importance of information and communication to promote diversity was identified, and the perception of conflicts in the library was also evaluated. Cultural diversity and cultural competence were considered in the organizational processes. The Case Study research method was applied. The findings consist of the following: the library has a management approach aligned with the goal of being a cultural reference locally for the various cultures, experiences, and subjectivities; library staff itself indicates the library's diversity perception and the importance of representativeness for the development and execution of intercultural projects; the information and communication between the library and the public assist with the commitment of diversity; the library aims to promote activities that help different social groups. The survey concluded that the development of competences at the individual and organizational levels is the solution to achieve coexistence and integration of multicultural groups. Thus, cultural competence demands actions that involve efficient information and communication flows between groups of distinct individuals; this can enhance the diversity management in organizations.
Competencia cultural en la gestión de la diversidad: estudio de caso en una biblioteca pública
Competência culturalnana gestãodada diversidade:estudoestudode decasocasoem emuma uma biblioteca pública
Keywords: Accessibility; Brazil; Cultural diversity; Library planning; Public library; Representativeness